Effect of Al on Microstructure and Properties of Hot-Rolled 2205 Dual Stainless Steel - Qian Meng; Peiqing La; Liang Yao; Peng Zhang; Yupeng Wei; Xin Guo (Advances in Materials Science and Engineering)
The microstructure, mechanical properties, oxidation, and corrosion resistance of 2205 stainless steels without and with Al in a range of 0.5 to 2.5 wt.% were investigated in this paper. The results showed that the matrix phase transformed from austenite to ferrite. The volume fraction of the ferrite in the steels decreased at first and then increased and was the lowest in the steel with 0.5 wt.% Al. Most of the Al was dissolved in the ferrite and austenite phases in the steels. The ultimate tensile strength and elongation rate of the steels increased at first and then decreased with the increasing Al content, with the highest values in the steel with 0.5 wt.% Al. The yield strength of the steels slightly increased from 544 to 607 MPa due to the addition of Al. The oxidation rates of the steels with Al were much lower than that of the steel without Al, and the rate of the steel with 1.5 wt.% Al was the lowest, approximately 10 times lower than that of the steel without Al. The corrosion rates of the steels with 0.5 and 1.0 wt.% Al were slightly higher than that of the alloy without Al. In general, the steel with 1 wt.% Al had optimal properties.